Hyperoxia therapy for prevention of postoperative nausea and vomiting after breast cancer surgery - Mihalek Nora; Radovanović Dragana; Starčević Sanja; Vukoje Jelena; Juhas Daniel (Vojnosanitetski Pregled)
Background/Aim. Postoperative nausea and vomiting (PONV) are one of the most common causes of patient dissatisfaction in the postoperative period after general anesthesia. Hyperoxia may prevent PONV after abdominal surgery, but the effectiveness of intraoperative and early postoperative hyperoxia in preventing PONV after breast cancer surgery has not been fully elucidated. The aim of this study was to assess if the application of intraoperative hyperoxia during surgery could prevent PONV. Methods. Forty female patients with breast cancer were recruited for the study, all of whom underwent surgical treatment of breast cancer with axillary sentinel node sampling or axillary lymph node dissection. A balanced general anesthesia was conducted, which was induced with propofol and maintained with sevofluran. Out of the 40 patients, 20 (in-tervention group) received a volatile gas mixture with a fraction of inspired oxygen (FiO2) of 0.8 L/min intraoperatively and, afterward, 3 L/min of oxygen via face mask for two hours after surgery. The other 20 patients (control group) received a FiO2 of 0.4 L/min during the surgery without further administration of oxygen in the early postoperative period. The presence and severity of PONV were assessed at 30 min, 4, 24, 32, 48, and 56 hrs after surgery with the use of the PONV numerical Intensity Scale by Wengritzky for evaluating clinically significant PONV in the first six hours after surgery. Data were collected in an Excel spreadsheet and analyzed using the independent Student’s t-test. Results. The overall incidence of PONV during the 30 min after the surgery was 17.5% (15% in the group of patients receiving FiO2 of 0.8 L/min and 20% in the group of patients receiving FiO2 of 0.4 L/min intraoperatively). There was no statistically significant difference between the two groups in the frequency of PONV, as well as in the severity of PONV, measured with the PONV Intensity Scale by Wengritzky (p ≥ 0.05). Conclusion. We found no benefit of intra- and post-operative hyperoxia in reducing the incidence of PONV. The data do not support routine administration of hyperoxia, in addition to antiemetics, for the prevention of PONV in patients undergoing breast cancer surgery.